Biomechanical Approach to Improve the Abdominal Aortic Aneurysm (AAA) Rupture Risk Prediction - Vilalta, Guillermo; Nieto, Félix; Norberto, Enrique San; Pérez, María Ángeles; Vilalta, José A.; Vaquero, Carlos (IntechOpen, 2012)
None